A Study on Learning Analytics with Recommended System - et. al., N.UttejKumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education data mining is becoming popularfrom the education data we can derives the insights using data mining techniques. Insights which are used for students, faculty, and education organizations and one of the famous applications in data mining is recommender system. In the field of learning analytics recommender system have become common in recent years. In education sector student performance can increase by using different tools, which are used in recommender system application implementation. The style and expectations of the user should be correctly constructed to include the most appropriate suggestions. Researchers have proposed various types of recommender systems in learning analytics (RSL).The authors of this paper reviewed several current state of recommendation system models and presented their selection criteria in learning analytics. Authors investigated various significant preference factors and classified them based on their similarity in the RS (Recommender System).This article presents the future directions of RSL (Recommender Method in Learning Analytics) models and compiles a detailed.